FACTOR INFLUENCING FIRST TIME VOTERS PARTICIPATION IN 2024 PRESIDENTIAL ELECTION: A STUDY IN SEMARANG CITY - Siregar, Theresia Nadya Regina Winarno; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2024)
The 2024 Presidential Election which will be faced in the near future is a big topic of conversation among the general public. Not to mention, the General Election Commission predicts that there will be a surge in first time voters. First time voters are citizens who are registered as voters with the election organizers and are voting for the first time in an election in Indonesia between the ages of 17 and 21 years. The group that has just used its right to vote is known as first time voters in the political category. The political orientation of first time voters is always changing and will change according to the situation and variables that influence it. In Semarang itself, there are 26.031 first time voters who have been registered as permanent voters for the 2024 Presidential Election. This research aims to determine the enthusiasm of first time voters in Semarang City in the 2024 Presidential Election and what factors can influence them. This research was conducted using quantitative methods with descriptive and inferential approaches. Data collection was carried out by distributing questionnaires to various districts in Semarang City. The sample size for this research was 205 respondents. The research results show that the enthusiasm of first time voters in Semarang City in the 2024 Presidential Election is in very good level. This is proven by their interest in participating in the campaign, using their right to vote, and their criticality in assessing the candidates. This is certainly a breath of fresh air because based on several previous studies, first time voters in several regions in Indonesia are not very interested in participating in the 2024 Presidential Election and previous periods